IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN RELIGIUSITAS SISWA DI SMP MARTIA BHAKTI BEKASI - Mansur Mansur (Asaatidzah, 2022)
This study aims to describe the concept of transformational leaders in increasing student religiousity at Martia Bhakti Junior High School, Bekasi City. Because religious attitude is one indicator of the very low moral personality of students at Martia Bhakti Middle School, Bekasi City. This research is a qualitative research that uses a phenomenological approach. Sources of data, namely primary data sourced from principals, schools, teachers, students. Meanwhile, secondary data were taken from documents related to the research. The instrument used in collecting data is the researcher himself who functions to determine and select informants as data sources, analyze data, interpret data, and the instruments in collecting data are observation, interviews, and documentation. The results showed that the success of transformational leaders at Marta Bhakti Middle School in Bekasi City, can be seen in terms of how much change there is in the teachers and employees of Marta Bhakti Middle School Bekasi City. In this case, it can also be seen from two aspects, the first is the aspect of awareness and the second is the social aspect. Success in terms of awareness is seen from the practice or application of school principal planning related to the religious atmosphere.